Knowledge and attitudes toward preventing hospital-acquired infections among nurses and residents at a university hospital - Mazin Barry; Ghada Alhadlaq; Reem Alsergani; Rana Almana; Nora Alshabib; Najd Altheeb (Wolters Kluwer Medknow Publications, 2020)
Introduction: Survey questionnaire hospital-acquired infections (HAIs) can be prevented through correct prevention and control measures. We assessed knowledge and attitudes of nurses and postgraduate residents in a developing country, by comparing knowledge on HAI and its prevention between internal medicine and surgery residents and between nurses in outpatient departments, wards, and intensive care units (ICUs) to assess need on more focused training. Methodology: This was a cross-sectional study measuring the knowledge and attitudes on HAI among 261 health-care workers. A questionnaire was adapted from the Centers for Disease Control and Prevention and World Health Organization. The association between knowledge score percentage and demographic and work-related factors was assessed using independent samples t-test or one-way analysis of variance when appropriate. The Chi-square test (Fisher's exact test when appropriate) was used to compare the percentage of correct answers between residents and nurses. Results: Nurses and residents did not meet the accepted level of knowledge, with mean scores of 71.2% among 160 nurses and 66% among 101 residents. Nurses' knowledge score was significantly associated with their department (P < 0.001). Nurses working in ICUs had a higher mean knowledge score (81.68%) than nurses working in outpatient (56.77%) or inpatient (72.5%) settings. Whereas, no significant difference is found among residents' mean knowledge score according to their departments. Conclusions: Residents and nurses had insufficient knowledge regarding HAI prevention varying by department. Corrective measures through increased education and training intensively targeting specified areas would be helpful in improving knowledge and preventing infections.